Active Noise Cancellation for Predefined Voices - Venkata Ram Reddy, D; V. Prabhu, A; Sri Krishna Chaitanya, M; K, Gopiram (International Journal of Engineering and Technology, 2018)
This paper describes the Active noise cancellation for predefined voice. It is another technique of cancelling the noise with adaptive filter. Its Pros lies in this, with no apriority evaluations of noise, we can decrease the noise reduction, or we can try to decrease the strength by designing the filters. If we can’t find the frequency of the signal, we have to design fixed filter. It wants two inputs one is primary input which contain voice and some noise and a reference input containing noise. And the second input is the reference input which is filtered, and we can hear it with noise reduction and we can see it signal representation. Active filtering before subtraction allows the treatment of data sources that square measure settled or arbitrary, stationary or time-variable. Further this project can be developed by taking the two voices at a time and we can hear a single voice which is filtered.